God and grace of body: sacrament in ordinary - Brown, David (Oxford University Press, 2007)
David Brown explores the ways in which the symbolic associations of the body and what we do with it have helped shape religious experience and continue to do so. A Church narrowly focused on Christ's body wracked in pain needs to be reminded that the body as beautiful and sexual has also played a crucial role not only in other religions but also in the history of Christianity itself. Dance was one way in which the connection was expressed. The irony is not that such a connection hasgone but that it now exists almost wholly outside the Church. Much the same could be said about music more genera